PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KANTOR DINAS PENDIDIKAN KOTA PADANG - Sutiyem Sutiyem; Jumiatul Mulya; Nova Gustika (Universitas Dharma Andalas, 2019)
This study aims to identify and analyze transformational leadership on performance. Office of Education Office of Padang City and to find out and increase assistance for the Office of Education Office of Padang City. The type of research conducted is an associative quantitative research. The sample in this study amounted to 159 respondents, namely employees of Education Office of Padang. The data were collected in the form of questionnaire and analysis with the help of SPSS ver software. 22.0. The results in this study indicate that the variable transformational leadership positive and significant with regression coefficient value of 0.726 to the performance of the Education Office of the city of Padang. The variable of positive and significant work motivation with regression coefficient value equal to 0,164 to performance of Education Office office of Padang. The value of R2 is 0.768. This can be interpreted that transformational leadership and work motivation is a factor capable of performance with percentage of 76.8%, while the remaining 23.2% by factors not used in this study, environmental factors, and organizational commitment factors.